Ephemeroptera from the Venezuelan Guayanas´s Uplands: Families Leptophlebiidae, Euthyplociidae and Oligoneuriidae - Dominguez, Eduardo (2014)
As a continuation of a series of papers to improve the knowledge of the Ephemeroptera fauna of the Venezuelan Guayana´s Uplands, an update of the families Leptophlebiidae, Euthyplociidae and Oligoneuriidae in the region is presented. As a result, Paramaka incognita sp. nov. is described, the female of Askola emmerichi is described for the first time, and the genera Askola, Hydrosmilodon and Leentvaaria, the subgenus Miroculis (Atroari) and the species Miroculis (M.) marauiae are recorded for the first time for Venezuela.